Solutions of time-fractional third- and fifth-order Korteweg–de-Vries equations using homotopy perturbation transform method. Issue 7 (12th August 2019) - Karunakar, Perumandla; Chakraverty, Snehashish
Abstract : Purpose: This study aims to find the solution of time-fractional Korteweg–de-Vries (tfKdV) equations which may be used for modeling various wave phenomena using homotopy perturbation transform method (HPTM). Design/methodology/approach: HPTM, which consists of mainly two parts, the first part is the application of Laplace transform to the differential equation and the second part is finding the convergent series-type solution using homotopy perturbation method (HPM), based on He's polynomials. Findings: The study obtained the solution of tfKdV equations. An existing result "as the fractional order of KdV equation given in the first example decreases the wave bifurcates into two peaks" is confirmed with present results by HPTM. A worth mentioning point may be noted from the results is that the number of terms required for acquiring the convergent solution may not be the same for different time-fractional orders. Originality/value: Although third-order tfKdV and mKdV equations have already been solved by ADM and HPM, respectively, the fifth-order tfKdV equation has not been solved yet. Accordingly, here HPTM is applied to two tfKdV equations of order three and five which are used for modeling various wave phenomena. The results of third-order KdV and KdV equations are compared with existing results.